North East Frontier Agency Review of Progress of Development Activities for the Year 1965-66 - Planning Commission (Planning Commission, 1967)
The year 1965-66 i.e. the last year of the Third Plan, envisaged and outlay of Rs.273,74 lakhs against which the Budget grant was Rs.223,37 lakhs. An expenditure of Rs.220.19 was incurred during the year under report, thus bringing the total expenditure to Rs.732.39 lakhs for the entire plan period against the Plan provision of Rs.715.00 lakhs. The break up of the Budget grant and the expenditure incurred during 1965-66 is given below department wise
Review of Progress of Development Activities for the Year 1965-66
Government of Meghalaya